Microbiological Justification of the Germicide Selection for the Treatment of Salmonellosis in Children - L. P. Zharkova; N. N. Smolyankin; A. I. Grekova; S. N. Kozlov (Антибиотики и Химиотерапия, 2020)
The article presents the data on determination of sensitivity of Salmonella strains in vitro by the method of serial dilutions in broth with the determination of the minimum inhibitory concentrations (MIC) to antimicrobial agents in accordance with the 2015 EUCAST (European Committee on Antimicrobial Susceptibility Testing European Committee for determination of sensitivity to antimicrobial agents) criteria and national clinical guidelines. The study demonstrated a high pharmacodynamic activity of the III generation cephalosporins (Cefotaxime, cefepime), azithromycin, co-trimoxazole and the presence of Salmonella with resistance to ciprofloxacin (24.3%).